Prevalence and risk factors of metabolic syndrome in obese and non-obese South Indian adults: A population-based cross-sectional study - Rana, Raju; Kamath, Shobha U; Shastri, B Ananthakrishna; U, Shashikiran; Maiya, G Arun; Kamath, Ullas; Rao S, Raghavendra; Lakshmi R, Vani (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Metabolic syndrome (MetS), a cluster of risk factors associated with various noncommunicable diseases, has traditionally been linked to obesity. However, recent studies have demonstrated high MetS prevalence among non-obese individuals, with evidence suggesting distinct patterns of lifestyle risk factors between obese and non-obese populations. This study aims to estimate the prevalence of MetS in non-obese individuals and investigate the independent associations between lifestyle risk factors and MetS in both obese and non-obese populations.Methods: A total of 443 participants were recruited, comprising 177 non-obese and 266 obese individuals in this study. Data were collected on family history, physical activity levels, smoking status, alcohol consumption patterns, and dietary intake of fruits and vegetables. Obesity was classified according to Asia-Pacific criteria, with non-obese defined as (BMI